Energy transfer mechanisms in CdSe/CdS nanorod heterostructures. - Ngiam, Song Wee. (2011)
A series of time-resolved transient absorption spectroscopy experiments were performed on ensembles of CdSe/CdS dot/rod nano-hetero-structures dispersed in toluene. The resulting decay dynamics were quantified via data fitting of the differential transmission of probe laser pulses to multi-exponential decay functions. The lifetimes extracted from the data fit indicates the timescales over which the recombination processes within the system of study occur.